PELATIHAN PEMBUATAN GAME UNTUK SISWA SMA SANTA MARIA 1 CIREBON MENGGUNAKAN APLIKASI SCRATCH - Adelia Adelia; Djoni Setiawan (Politeknik Negeri Sriwijaya, 2022)
Knowledge can be shared in the form of teaching or training. The training was given to the Santa Maria 1 Cirebon High School, online during the current Covid-19 pandemic. The training is given to meet the needs of schools that want to add to the teaching materials that have been given in the field of programming to students, develop students' abilities in logic, think systematically and help students understand simple programming. To help meet the needs of the school, training was provided by Maranatha Christian University, especially the Information Technology Faculty, to class X students, by providing training to make online games using zoom. Game making training given to students, using the scratch application. The scratch application is used to support the fulfillment of school needs, introduce applications that can be easily learned by students and share knowledge possessed by lecturers of the Faculty of Information Technology. At the end of the training, students can follow the training well and can create games using the scratch application.